Securitising Singapore State Power and Global Threats Management - Syed Mohammed Ad’ha Aljunied (2019)
Aljunied examines how the Singaporean government developed a comprehensive state–society strategic relationship by ‘securitising’ vital policy areas because of Singapore’s vulnerability as a global city state.